A sort of friend: narratives from young people and parents about collaboration with a mental health outreach team. Issue 4 (3rd July 2020) - Soggiu, Anna-Sabina Lindroos; Klevan, Trude; Davidson, Larry; Karlsson, Bengt
ABSTRACT: Mental health issues among young people have received increasing attention in Norway as more are diagnosed with and report mental health problems. In this study, we focus on the personal and social recovery processes of young people with mental health difficulties. The aim of the study was to explore how young people and parents experience collaboration with a community-based mental health outreach team around recovery processes, using a narrative analysis. Three topics from the findings are discussed: relationships and collaborations built on the service user's goals, closeness and distance in professional helping relationships, and comprehension of professionalism.